2021
DOI: 10.1505/146554821832140394
|View full text |Cite
|
Sign up to set email alerts
|

Forest governance in DRC: an analysis from actors' participation in REDD+ policy development

Abstract: The Democratic Republic of Congo (DRC) has implemented Reduced Emissions from Deforestation and forest Degradation (REDD+), a process that requires inclusive decision making and accountability. Our research analyses the participation of policy actors in DRC by asking: (1) Who is involved in national REDD+ policy making and what is their interest in participating in core policy events? (2) What level of participation do the different political actors have in core policy events? (3) To what extent do the outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Literature indicates that communities participate more in PFM when they have a village forest (Banana et al 2012;Chang and Andersson 2021;Mukasa et al 2012;Pham et al 2021;Riggs et al 2021;Schweizer et al 2021;Wilson and Cagalanan 2016;Zulu 2013). Zulu (2013) reported that having a VFA had significant synergistic effects on communities' participation in various co-management activities under IFMSLP.…”
Section: Performance Of Pfm With Regard To Communities' Participation...mentioning
confidence: 99%
“…Literature indicates that communities participate more in PFM when they have a village forest (Banana et al 2012;Chang and Andersson 2021;Mukasa et al 2012;Pham et al 2021;Riggs et al 2021;Schweizer et al 2021;Wilson and Cagalanan 2016;Zulu 2013). Zulu (2013) reported that having a VFA had significant synergistic effects on communities' participation in various co-management activities under IFMSLP.…”
Section: Performance Of Pfm With Regard To Communities' Participation...mentioning
confidence: 99%
“…Literature indicates that communities participate more in PFM when they have a village forest (Banana et al 2012;Chang and Andersson 2021;Mukasa et al 2012;Pham et al 2021;Riggs et al 2021;Schweizer et al 2021;Wilson and Cagalanan 2016;Zulu 2013). Zulu (2013) reported that having a VFA had significant synergistic effects on communities' participation in various co-management activities under IFMSLP.…”
Section: Performance Of Pfm With Regard To Communities' Participation...mentioning
confidence: 99%